2016
DOI: 10.1111/pedi.12420
|View full text |Cite
|
Sign up to set email alerts
|

Severity of clinical presentation in youth with type 1 diabetes is associated with differences in brain structure

Abstract: Objective Differences in cognition and brain structure have been found in youth with type 1 diabetes compared to controls, even after relatively short disease duration. To determine whether severity of clinical presentation contributes to these differences, we obtained structural MRI scans in youth ages 7–17 who were either newly diagnosed with type 1 diabetes (<3.5 months from diagnosis, n=46) or a sibling without diabetes (n=28). Research Design and Methods Severity of presentation was measured by the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 50 publications
3
30
0
3
Order By: Relevance
“…13,2224 Subtle brain injury often occurs during treatment for diabetic ketoacidosis in children and may contribute to cognitive decline. 49 Excessive fluid administration, which may result in rapid osmotic changes, has been widely suspected to cause brain injury, 11,25,26 but a more recent hypothesis suggests that cerebral hypoperfusion and the effects of reperfusion, along with neuroinflammation, are central to diabetic ketoacidosis–related brain injury. 2,2729 The latter hypothesis is consistent with reports that document symptomatic and even fatal brain injury occurring before the initiation of treatment for diabetic ketoacidosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,2224 Subtle brain injury often occurs during treatment for diabetic ketoacidosis in children and may contribute to cognitive decline. 49 Excessive fluid administration, which may result in rapid osmotic changes, has been widely suspected to cause brain injury, 11,25,26 but a more recent hypothesis suggests that cerebral hypoperfusion and the effects of reperfusion, along with neuroinflammation, are central to diabetic ketoacidosis–related brain injury. 2,2729 The latter hypothesis is consistent with reports that document symptomatic and even fatal brain injury occurring before the initiation of treatment for diabetic ketoacidosis.…”
Section: Discussionmentioning
confidence: 99%
“…13 Among patients without obvious neurologic decline during treatment for diabetic ketoacidosis, subtle neurologic alterations are often present after recovery, including deficits in memory, attention, and IQ 47 and changes in cerebral microstructure. 4,8,9 …”
mentioning
confidence: 99%
“…Similarly, previous studies provide supporting evidence that the structural and neurometabolic alterations related to T1DM, which is usually diagnosed during childhood, may be prominent particularly in the fronto‐temporo‐parietal regions . Considering the well‐known microvascular alterations of white matter (WM) in prolonged hyperglycemic conditions, it is important to focus on the fronto‐temporo‐parietal WM regions in investigating T1DM‐related brain structural abnormalities …”
Section: Introductionmentioning
confidence: 78%
“…In this study, we examined fractional anisotropy (FA), a sensitive marker for microstructural alterations in WM integrity, in both young adults with T1DM as well as healthy individuals using diffusion tensor imaging (DTI). We expected to observe T1DM‐related deficits in the fronto‐temporo‐parietal WM regions . In addition, we focused on the working memory domain as a neurocognitive substrate of T1DM‐related fronto‐temporo‐parietal WM deficits, considering its significant role in memory‐related processes .…”
Section: Introductionmentioning
confidence: 99%
“…[2,7,17] Magnetic resonance imaging studies have demonstrated changes in cerebral microstructure associated with DKA in children. [22] In addition, previous data from studies by our group have shown that DKA acutely causes reactive astrogliosis and activation of microglia in the brains of juvenile rats and that these findings are most prominent in the hippocampus. [17] The current data extend these findings to demonstrate that reactive astrogliosis does not resolve after DKA recovery but instead results in permanent alterations in hippocampal microstructure.…”
Section: Alterations In Cognition Have Been Well Documented In Both Cmentioning
confidence: 90%